2017
DOI: 10.1590/1518-8345.1658.2840
|View full text |Cite
|
Sign up to set email alerts
|

Perceptional gaps among women, husbands and family members about intentions for birthplace: a cross-sectional study

Abstract: Objective:women are more likely to give birth at a health facility when their families agree with the birthplace. However, in rural areas of Tanzania, women are often marginalized from decision-making. This study predicted birthplace intention and identified factors to reduce perceptional gaps among pregnant women, husbands and family members. Method:explanatory cross-sectional survey was conducted in three villages in North Eastern Tanzania. Participants were 138 pregnant women and their families who answered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As the ‘ANC visit more than 4 times’ is an important factor that affects other outcomes [15, 16], the birth outcome variables were adjusted for ANC visits. Table 4 shows the ORs of the birth outcome variables in the comparison between the intervention group and the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the ‘ANC visit more than 4 times’ is an important factor that affects other outcomes [15, 16], the birth outcome variables were adjusted for ANC visits. Table 4 shows the ORs of the birth outcome variables in the comparison between the intervention group and the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the change in women’s involvement in decision-making for their birthplace had a unique cultural aspect that warrants discussion. In Tanzanian culture, many women lack the decision-making power within the family which hinders their birth preparedness particularly on transportation and birthplace as those require financial preparation [11, 12, 19, 20]. Moshi and Nyamhanga reported that men perceived their role in providing financial support; however, they tended to be less concerned about birthplace because they considered birth as women’s role [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Socio demographic, attended ANC, experienced complications, knowledge of danger signs -Descriptive statistics and logistic regression See Table 3 1. † Shimpuku, Madeni, Horiuchi&Leshabari (2017) [ 38 ] To assess predicted birthplace intentions Pregnant women ≥16, (no psychological or physical illness), husbands and family members ≥16living with women (121: 42 pregnant women, 35 husbands and 44 family members) Non-probability sampling and purposive sampling via village leaders for pregnant women - Cross-sectional observational study −38 item study-specific birth intention questionnaire -Chi-square test, ANOVA, multiple regression, correlation See Table 3 .59† Uganda Kakaire, Kaye & Osinde (2011) [ 39 ] To assess factors associated with BPCR & level of male participation in the birth plan among emergency obstetric referrals Pregnant women admitted as emergency obstetric referrals Average for women and men: age 26, 32, 73 and 55% had no or primary education, 81% married (140) Purposive sampling for referrals Healthcare workers recruited participants - Cross-sectional observational study - Questionnaire: Socio-demographic, medical history, Birth preparedness, roles of spouses in birth plan -Medical records: obstetric complications, reasons for referral, obstetric care obtained at the referral and referring sites and availability of a birth plan - Frequencies, Chi-square test. Bivariate logistic regression.…”
Section: Resultsmentioning
confidence: 99%